City Diplomacy, Multilateral Networks and the Role of Southeast Asia - Der-yuan Wu (Global Strategis, 2020)
In the wake of globalization, cities have increasingly engaged in international affairs. Positioning as in-between administrative entities and to reconcile between competing national interests and universal objectives like the UN Sustainable Development Goals (SDGs), cities could demonstrate their agency in providing alternative pursuit of global development. In particular, while international affairs have in a way environmentalized, global environmentalism in turn has strongly urbanized in recent decades. Many cities along the coast, in Asia or broader world alike, are at the forefront of climate change impacts and would be vulnerable to any catastrophes such as the Indian Ocean tsunami of 2004. After all, given the size of city economies, the material losses caused by climate-induced extreme weather can be tremendous. Thus, it is worthwhile to examine the role of Southeast Asian cities in international development in terms of their transnational networking. Moreover, the phenomenon that cities becoming active players in international affairs has been explored mostly in relation to North American, European or Western setting. Literature on cities’ transnational and multi-level engagement in the EU has been abundant. By contrast, there is very few researches focusing on the part of ASEAN in mainstream literature on city diplomacy or paradiplomacy. The primary purpose of this paper is thus to examine the state of play by Southeast Asian cities in some key multilateral networkings such as C40 Cities, International Council for Local Environmental Initiatives (ICLEI) and United Cities and Local Governments (UCLG).Keywords: city diplomacy, Southeast Asia, transnational networking, multilateral networkingKota-kota semakin terlibat dalam urusan internasional setelah globalisasi mulai muncul ke permukaan. Memposisikan sebagai entitas administratif di antara dan untuk merekonsiliasi antara kepentingan nasional yang bersaing dan tujuan universal seperti Tujuan Pembangunan Berkelanjutan PBB (SDGs), kota-kota dapat menunjukkan peran mereka dalam memberikan alternatif pengejaran pembangunan global. Lebih lanjut, ketika isu lingkungan telah mendominasi dunia internasional, para pemikir lingkungan global telah membuatnya menjadi lebih urban dalam beberapa dekade. Banyak kota di daerah pantai, baik di regional Asia ataupun di regional lainnya di dunia, berada dalam resiko tinggi akan perubahan iklim dan rentan terhadap bencana seperti tsunami, seperti yang terjadi di Samudra Hindia tahun 2004. Terlebih lagi, mengingat ukuran ekonomi kota, kerugian materiil disebabkan oleh cuaca ekstrem yang disebabkan oleh iklim cenderung cukup besar. Dengan demikian, ada baiknya untuk memeriksa peran kota-kota Asia Tenggara dalam pengembangan internasional dalam hal jaringan transnasional mereka. Selain itu, fenomena bahwa kota menjadi pemain aktif dalam urusan internasional telah dieksplorasi sebagian besar di kawasan Amerika Utara, Eropa atau Barat. Literatur tentang keterlibatan transnasional dan multi-level kota-kota di Uni Eropa telah berlimpah. Sebaliknya, masih sedikit penelitian yang berfokus pada bagian ASEAN dalam literatur arus utama tentang diplomasi kota atau paradiplomasi. Tujuan utama dari tulisan prospektif ini adalah untuk menguji keadaan permainan oleh kota-kota Asia Tenggara di beberapa jaringan multilateral utama seperti Kota C40, Dewan Internasional untuk Inisiatif Lingkungan Lokal (ICLEI) dan United Cities and Local Governments (UCLG).Kata-Kata Kunci: diplomasi antar kota, Asia Tenggara, jaringan transnasional, jaringan multilateral